Pekanbaru Youth Centre Dengan Pendekatan Arsitektur Perilaku - Reghina Tri Municha; Pedia Aldy; Mira Dharma S (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
As the era develops, youth activity becomes more and more various. Unfortunately, it is not well-provided as we lack some facilities. One of the facilities needed to solve this problem is Youth Centre. It is a centre unit where young people can have such activities concerning retreat, innovation and talent’s growth. Young People, as we know having bold and dynamic characters, tend to pursue freedom, have much curiosity to try something nwe, and be active in social life. Therefore, in designing a suitable youth centre for them, use character and mosaic concept as a ethod to facilitate their activities.this concept represent their characters in finding their own talents and interest with changing rates and colors which shows their differences. By using this, find out some more activities needed in sports, arts and social which can affect the textures, colors, circulation and any other facilities. The aim of writing this thesis is to make young people feel comfortable doing any activities they want.Keyword: Youth Center, Youth, Teenager, Behavior Architecture, Talent and Interest.